Stalinowskie represje wobec Edwarda Kuli, nauczyciela historii, w świetle dokumentów Wojskowego Sądu Rejonowego w Zielonej Górze = Stalinist repression against history teacher Edward Kula in the light of files of Circuit Military Court in Zielona Góra - Budniak, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The life of Edward Kula, a History and head teacher, deserves describing not only because he became a victim of Stalinist terror, directed at its ideological opponents, as he had been named by the communist authorities, but also because he was made a second-class citizen who, having served a prison sentence, was made to live a life of a social outcast.
Keywords: represje stalinowskie; Powiatowy Urząd Bezpieczeństwa Publicznego w Zielonej Górze; Wojskowy Sąd Rejonowy w Zielonej Górze; Polska Ludowa - szkolnictwo; Nauczyciele - Polska - po 1944 r.; Kula, Edward (nauczyciel; 1914-1999); stalinist repression; Office of Public Security in Zielona Góra; Military District Court in Zielona Góra